Word Formation: A Morphological Analysis - Raja, Viator Lumban (Journal of Language and Literature, 2014)
New words are required not only to increase our vocabulary but also to create new sentences. New words are acquired by the process of word formation which can be done in several ways. One of the most commonly used ways to form new words is affixation either through prefixation or suffixation. Confixation or infixation is hardly ever used and is evidenced in the Indonesian Language. Other methods of word formation include coining, clipping, blending, acronym, and compounding. A difficulty arises when one has to decide which morpheme comes first, if he encounters a word with bound morphemes at both sides, since the two bound morphemes are not simultaneously attached to the root. Confixation occurs when morphemes are bounded both ends of the root simultaneously. Confixation can be seen in the Indonesian language. Key words: word formation, bound morphemes at both sides